Interprofessional communication in a psychiatric outpatient unit - an ethnographic study - Ingela Rudberg; Annakarin Olsson; Charlotta Thunborg; Martin Salzmann-Erikson (BMC, 2023)
Abstract Background Communication in healthcare has been extensively studied, but most research has focused on miscommunication and the importance of communication for patient safety. Previous research on interprofessional communication has mainly focused on relationships between physicians and nurses in non-psychiatric settings. Since communication is one of the core competencies in psychiatric care, more research on interprofessional communication between other clinicians is needed, and should be explored from a broader perspective. This study aimed to explore and describe interprofessional communication in a psychiatric outpatient unit. Method During spring 2022, data consisting of over 100 h of fieldwork were collected from observations, formal semi-structured interviews and informal conversations inspired by the focused ethnography method. Data was collected at an outpatient unit in central Sweden, and various clinicians participated in the study. The data analysis was a back-and-forth process between initial codes and emerging themes, but also cyclical as the data analysis process was ongoing and repeated and took place simultaneously with the data collection. Results We found that a workplace's history, clinicians´ workload, responsibilities and hierarchies influence interprofessional communication. The results showed that the prerequisites for interprofessional communication were created through the unit's code of conduct, clear and engaging leadership, and trust in the ability of the various clinicians to perform new tasks. Conclusion Our results indicate that leadership, an involving working style, and an environment where speaking up is encouraged and valued can foster interprofessional communication and respect for each other´s professional roles is key to achieving this. Interprofessional communication between different clinicians is an important part of psychiatric outpatient work, where efficiency, insufficient staffing and long patient queues are commonplace. Research can help shed light on these parts by highlighting aspects influencing communication.